Art and Social Justice Education : Culture as Commons. - Quinn, Therese (Taylor & Francis, 2011)
Art and Social Justice Education offers inspiration and tools for educators to craft critical, meaningful, and transformative arts education curriculum and arts integration projects. The images, descriptive texts, essays, and resources are grounded within a clear social justice framework and linked to ideas about culture as commons. Essays and a section written by and for teachers who have already incorporated contemporary artists and ideas into their curriculums help readers to imagine ways to use the content in their own settings. This book is enhanced by a Companion Website (www.routledge.c.